Integrated Agri-Supply Chain and Impact of Latest Farm Bills in India - Binish Paul, Dr. S. Umamaheswari (Mathematical Statistician and Engineering Applications, 2022)
A variety of procedures must be completed before agricultural products can reach the market, including harvesting, threshing, winnowing, bagging, shipping, storage, processing, and exchange. Numerous nationwide studies have demonstrated that there are considerable agricultural productivity losses at each of these stages. The Ministry of Food and Civil Supplies, Government of India, most recently calculated the total avoidable post-harvest losses of food grains. 20 million Mt of post-harvest losses each year are a major, avoidable waste in a country where 20% of the population is undernourished. According to World Bank research, post-harvest losses of food grains in India account for 8–10% of overall production from farm to market and 4.5-5% of the total at the market. It is evident that post-harvest losses have an impact on the macro and local levels of the economy. This article provides a critical assessment of the state of agriculture supply chain management today. Topics covered include the role of agriculture supply chain management, Agri-food supply chain management, elements of the Agri-supply chain, Agri marketing, the emergence of coordinated supply chains in India, and the effects of farm bills. These actions will speed up the growth of the agricultural sector by giving farmers access to more marketing and storage tools, like cold storage networks. The creation of new jobs will increase as the economy grows. Initiatives are being taken to prevent food waste as the government comes to recognise the worth of farmers and agricultural produce. The farm legislation have additional advantages.